A Narrative Study of the Impact of Digital Leadership Training on the Learning Motivation of Engineering Students - Rosnelli , Rosnelli; Mukminin , Amirul (Insight: the psychological dimensions of society, 2025)
The purpose of this study was to explore engineering students’ perspectives on the impact of digital transformation leadership training and its relationship to learning motivation. Methods. This study employed qualitative methods to explore participants’ experiences, perspectives, and behaviors within the context of the digital leadership training they participated in. Data collection techniques included semi-structured interviews with three civil engineering students, three electrical engineering students, and three mechanical engineering students who participated in the digital leadership training. The results, reviewed from the engineering students’ perspectives, revealed four main themes. These themes included digital simulation as a means of career preparation, active and collaborative participation in training that encourages digital skills enhancement, synergy with the industrial world as a platform for developing work competencies, and training that encourages creativity and innovation to address the challenges of the workplace. Discussion and conclusions. Based on the findings from the engineering students’ perspectives, several conclusions can be drawn. Digital simulation is effective for strengthening career readiness. Active and collaborative participation in training contributes to improving digital skills. Furthermore, the synergy between education and industry is crucial for developing work competencies. Finally, training that emphasizes creativity and innovation is key to adapting to the challenges of today’s dynamic work environment. This conclusion highlights that designing training programs to be contextual, collaborative, and industry-based is essential for effectively enhancing the work readiness of the younger generation. Such an approach ensures that students not only acquire theoretical knowledge but also develop practical competencies and soft skills that are directly applicable to the modern workplace. Suggestions for future research are to analyze the driving and inhibiting factors of student learning motivation based on these four themes to strengthen the design and implementation of training programs, so as to increase the readiness of engineering students to face the dynamics of industrial needs in the era of digital transformation.